Tinjauan Etika Bisnis Islam Dan Fiqih Muamalah Terhadap Praktik Jasa Keperantaraan Dalam Jual Beli Cabai Besar - Ratna Sari, Widya; Sulistyowati; Muntafarida, Binti; Novia Saka, Dijan; Subandono, Agus (Fakultas Syariah IAIN Kediri, 2024)
Brokerage services have experienced growth and development in the business world in society. Business actors, especially large chili farmers, are increasingly relying on intermediary services to facilitate the sale of their crops so that their income can be disbursed more quickly. The aim of this research is to explain the review of Islamic business ethics and muamalah fiqh on the practice of delivery services in buying and selling large chilies in Tegalan Village, Kandat District, Kediri Regency. This research uses a descriptive qualitative approach. Obtaining data through observation, interviews, and documentation is finally analyzed using data reduction, data presentation, and conclusions. Checking the validity of the data uses extended participation techniques, persistence or regularity of observations, and data triangulation. Research findings show that the review of Islamic business ethics which includes unity (tauḫid), equilibrium/balance (al-'adl), free will (free will), and responsibility (responsibility) has not been fully fulfilled in this practice. Furthermore, this practice is partly by the pillars and requirements of muamalah fiqh, namely aqid and ma'qud alaih, but what is not appropriate is related to maudhu' al-aqid and sighat of the contract. The practice of intermediary services in buying and selling large chilies in Tegalan Village, Kandat District, Kediri Regency, involves two transaction schemes. The basic difference between these schemes: there is an additional transaction in the second scheme, namely that the service provider provides capital loans to farmers. This practice uses a samsarah contract, where the intermediary who sells the farmer's chili does not bear the risk but instead charges operational costs to the farmer. These operational costs are not explained in detail to farmers and the prices agreed between intermediaries and market traders are not communicated to farmers.